2017
DOI: 10.1016/j.vaccine.2017.06.074
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of influenza vaccination recommendation and early vaccination uptake during the 2015–16 season among adults aged ≥18 years – United States

Abstract: Background Since 2010, the Advisory Committee on Immunization Practices (ACIP) has recommended that all persons aged ≥6 months receive annual influenza vaccination. Methods We analyzed data from the 2015 National Internet Flu Survey (NIFS), to assess knowledge and awareness of the influenza vaccination recommendation and early influenza vaccination coverage during the 2015–16 season among adults. Predictive marginals from a multivariable logistic regression model were used to identify factors independently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 41 publications
3
25
2
Order By: Relevance
“…While self-protection from influenza was the most common main reason given for vaccination in both those with and without high-risk household members, nearly 90% of vaccinated adults with high-risk household contacts reported that protection of those around them was one of the motivating factors in getting vaccinated. A recommendation and offer of influenza vaccination from a healthcare provider was associated with increased vaccination coverage among all adults in a previous analysis of NIFS data [14]. In the current analysis, adults with a high-risk household member who received an offer of vaccination from a healthcare provider had higher coverage than those without a high-risk household member who received a provider offer, suggesting further that having high-risk household contacts motivates vaccination.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…While self-protection from influenza was the most common main reason given for vaccination in both those with and without high-risk household members, nearly 90% of vaccinated adults with high-risk household contacts reported that protection of those around them was one of the motivating factors in getting vaccinated. A recommendation and offer of influenza vaccination from a healthcare provider was associated with increased vaccination coverage among all adults in a previous analysis of NIFS data [14]. In the current analysis, adults with a high-risk household member who received an offer of vaccination from a healthcare provider had higher coverage than those without a high-risk household member who received a provider offer, suggesting further that having high-risk household contacts motivates vaccination.…”
Section: Discussionmentioning
confidence: 46%
“…KnowledgePanel ® participants are initially chosen by a random selection of residential addresses and are continuously recruited. KnowledgePanel ® sampling methodology has been previously described elsewhere [14,15].…”
Section: Methodsmentioning
confidence: 99%
“…Our results are consistent with the results of many studies that have assessed the execution of vaccination, both in developing 22 and in developed countries such as Spain or the USA. 23,24 In those studies, higher education was associated with better implementation of the vaccination program. However, some studies do not confirm this relationship.…”
Section: Discussionmentioning
confidence: 93%
“…However, the proportion reporting receipt of a voucher was relatively low among men who were current smokers (Table 4). Socioeconomic deprivation is known to be associated with lower levels of knowledge about vaccinations [18] and vaccine uptake [19] among adults. Further effort is necessary to encourage participation among hard-to-reach groups.…”
Section: Discussionmentioning
confidence: 99%